SCREENING ANTIBACTERIAL ACTIVITY OF VIETNAMESE PLANT EXTRACTS AGAINST HUMAN PATHOGENIC BACTERIA - NGO, LONG HOANG; NGUYEN, THI HAI YEN; TRAN, VU KHAC; DOAN, VU VAN; NGUYEN, MINH VAN; BUI, HIEU TRUNG (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objectives: Infectious diseases caused by bacteria are a leading cause of death worldwide. Hence, the objectives of the study are aimed to evaluate the antibacterial activity against five human pathogenic bacteria of methanolic extracts from 66 plants collected from Vietnam. Methods: The broth microdilution method was used to determine the minimum inhibitory concentration (MIC) of methanol extracts of 66 plant species against five bacterial strains. Results: In this study, all the plant extracts were active against at least one train with MIC values ranging from 24 to 2048 μg/mL. Twenty-five plant extracts were active against all three Gram-positive bacteria (Bacillus cereus, Bacillus subtilis, and Staphylococcus aureus). Of these, the extracts of Macaranga trichocarpa (Rchb. f. and Zoll.) Mull. Arg. (Euphorbiaceae), Calophyllum inophyllum L. (Clusiaceae) and Caryodaphnopsis baviensis (Lecomte) Airy Shaw (Lauraceae) exhibited the highest antibacterial activity (MIC =24–128 μg/mL), followed by extracts of Betula alnoides Buch.- Ham. e × . D. Don (Betulaceae), Acronychia pedunculata (L.) Miq. (Rutaceae), Croton alpinus A. Chev. ex Gagnep. (Euphorbiaceae) (MIC =64–256 μg/mL). Furthermore, the extract of Rhus chinensis Mill. (Anacardiaceae) and Annona reticulata L. (Annonaceae) exhibited potent antibacterial activity against the two Bacillus species (MIC =32–64 μg/mL). Conclusion: Results of this study reveal that plant extracts from Vietnam have highly antibacterial activity against Gram-positive bacteria. These results suggest that Vietnamese plant extracts may be a rich source of antibacterial drugs.